Comparison between Erich arch bars and intermaxillary screws in maxillofacial fractures involving the dental occlusion: a meta-analysis. Issue 1 (January 2021) - Fernandes, I.A.; Lopes, A.B.S.; Fonseca, P.G.; da Silva Torres, A.; Rodrigues, A.B.; Galvão, E.L.; Falci, S.G.M.
Abstract: This systematic review aimed to compare the Erich arch bars (EABs) with intermaxillary fixation (IMF) screws in maxillofacial fractures involving dental occlusion on perioperative parameters. Four electronic databases were searched: MedLine (Pubmed), Web of Science, VHL, and Cochrane Library. Inclusion criteria comprised clinical trials comparing the two IMF methods, assessing at least one of the outcomes: occlusal stability, oral hygiene, quality of life, time to apply and remove IMF appliances, and complications. Risk of bias was evaluated through the Cochrane risk of bias tool. Fifteen papers were included in the qualitative analysis and 12 of those in the meta-analysis. Times for EABs application (mean difference (MD) 46.83; 95% confidence interval (CI): 30.63–63.02) and removal (MD 22.89; 95% CI 14.61–31.17) were longer compared with IMF screws. There is higher risk of glove perforation (risk ratio (RR) 3.81; 95% CI 2.41–6.04) and lower risk of iatrogenic injuries (RR 0.21; 95% CI 0.09–0.48) when placing EABs compared with IMF screws. No significant differences in plaque index were found (MD 1.07; 95% CI -0.17 to 2.31). The quality of this evidence ranged from very low to low and was mainly compromised by risk of bias assessment. Further studies are necessary to evaluate transurgical IMF stability and postoperative occlusal quality and quality of life when comparing EABs with IMF screws.